Polymer Structure and Conformation Alter the Antigenicity of Virus-like Particle–Polymer Conjugates - Lee, Parker W. (J Am Chem Soc, 2017)
Covalent conjugation of water-soluble polymers to proteins is critical for evading immune surveillance in the field of biopharmaceuticals. The most common and long-standing polymer modification is the attachment of methoxypoly(ethylene glycol) (mPEG), termed PEGylation, which has led to several clinically approved pharmaceuticals. Recent data indicate that brush-type polymers significantly enhance in vitro and in vivo properties. Herein, the polymer conformation of poly-(ethylene glycol) is detailed and compared with those of water-soluble polyacrylate and polynorbornene (PNB) when attached to icosahedral virus-like particles. Small-angle neutron scattering reveals vastly different polymer conformations of the multivalent conjugates. Immune recognition of conjugated particles was evaluated versus PEGylated particles, and PNB conjugation demonstrated the most effective shielding from antibody recognition.